SOME NATURAL PRODUCTS AND THEIR SECONDARY METABOLITES ATTRIBUTED TOWARDS DIABETIC CURE: A REVIEW - Abdurrazak, Muhammad; Rao, Mahadeva U. S.; Ado, Ahmad Bashir; Mohd, Khamsah Suryati; Zin, Thant (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Diabetes is one of the major health and development challenges of the 21st century. According to the International Diabetes Federation, there are currently more than 371 million people living with diabetes and another 28 million are at risk of developing the disease. Aside from conventional allopathic medicines, traditional/alternative therapy plays a substantial part in treating diabetes mellitus. In the final few decades eco-friendly, bio-friendly, cost effective and relatively safe plant-based medicines have gone from the periphery to the mainstream with the increased research in the area of traditional medication. Plant-based medications are preferable as mainly non-toxic, having typically fewer side effects, better compatibility with physiological flora, and availability at low-costs. However, secondary metabolites isolated from these plants (Diosmin, Tangeritin, Lycopene, Syringin etc., ) possess this antidiabetic property. The power of the herb/active compound to enhance glucose utilization and lower plasma glucose level in rats suffering from insulin deficiency suggests that these plant extracts/phytochemicals may be useful in the discussion of human diabetes. Â 